1999
DOI: 10.1063/1.479776
|View full text |Cite
|
Sign up to set email alerts
|

Fully atomistic modeling of an electric field poled guest-host nonlinear optical polymer

Abstract: Fully atomistic molecular modeling is performed on an electric field poled guest-host nonlinear optical polymer system at two different densities. The higher density ͑HD͒ represents a sub-T g system, while the lower density ͑LD͒ corresponds to a system above T g. The electric field alignment of dopants was studied by calculating ͗cos ͘ and ͗cos 3 ͘ and comparing with the theoretically predicted order parameters. For the LD system, the dipole orientational order achieved during 1.5 ns of NVT dynamics at 500 K w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 67 publications
2
61
0
Order By: Relevance
“…By coarse-graining the polymer, the computationally expensive C-H and C5 5O bonds are eliminated without compromising the dynamics of the ablation calculation [20,21]. The bonding potentials are hybrid harmonicMorse potentials to allow bonds to break under conditions of high temperatures and/or stress [21,22]. Angular potentials are harmonic in form and use a screening function to inhibit sudden energy fluctuations resulting from bond breaks.…”
Section: Computational Detailsmentioning
confidence: 99%
“…By coarse-graining the polymer, the computationally expensive C-H and C5 5O bonds are eliminated without compromising the dynamics of the ablation calculation [20,21]. The bonding potentials are hybrid harmonicMorse potentials to allow bonds to break under conditions of high temperatures and/or stress [21,22]. Angular potentials are harmonic in form and use a screening function to inhibit sudden energy fluctuations resulting from bond breaks.…”
Section: Computational Detailsmentioning
confidence: 99%
“…We shall later learn from Monte Carlo calculations 5,40,41 that this is not a good approximation for all samples of interest. Indeed, atomistic and modified atomistic kinetic Monte Carlo calculations 48 will be necessary to describe the behavior of some samples (e.g., those with high chromophore concentrations and for multi-chromophore-containing dendrimer structures). However, we have demonstrated that a simple model of rigid chromophores freely reorienting in an isotropic medium has the great advantage of permitting analytical expressions for electro-optic activity as a function of chromophore concentration to be derived and of permitting evaluation of the effect of chromophore shape upon electro-optic activity using numerical algorithms executed on personal computers.…”
Section: Molecular and Nanoscale Engineeringmentioning
confidence: 99%
“…This will typically involve use of a variant of atomistic Monte Carlo computation methods. 19,24 Robinson and coworkers have suggested a computationally efficient pseudo-atomistic Monte Carlo approach that treats sections of the overall structure that contain conjugated π-electrons as rigid objects while treating flexible segments in a fully atomistic manner. 25 Since π-conjugation restricts rotation about bonds, this is a reasonable approximation.…”
Section: Introductionmentioning
confidence: 99%